Pengaruh Permainan Puzzle terhadap Perkembangan Motorik Halus Anak Usia Dini - Elva M. Sumirat; Tiara Meilia Lamatiti; Rasqah Magfiratunnisaa; Qur'ana M. Yadasang; Nadiva Adelia Akilie; Fitra Mulyani Abdullah; Nurain Yusuf; Agiska Katili; Lisnawaty Atuna; Harmin H Bakum; Cika Aprilia Kuku; Dwiva Muzdalifah Daud; Nabila Sinto; Jaliha Kadir (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2026)
This study investigates how puzzle games affect the fine motor development of young children. This study uses a quantitative approach and a quasi-experimental design. The study involved 30 children aged between 4 and 6 years who were divided into two groups: an experimental group and a control group. The experimental group received an intervention in the form of puzzle-playing activities for four weeks, with an interval of two to three times a week. On the other hand, the control group did not receive any special treatment for routine learning activities. To collect data, standardized fine motor skills test instruments were used. These included eye-hand coordination, finger movement control, precision, and the ability to assemble and copy shapes. A t-test was used to analyze the data to determine the difference in results between the two groups. The results of the study showed that the experimental group and the control group differed significantly. Compared to children who did not receive treatment, children who were involved in puzzle-playing activities showed greater improvement in all fine motor indicators. The results show that puzzle games can be used effectively as a learning tool to help the fine motor development of early childhood develop well.